The Valuation of Default-Triggered Credit Derivatives - Chen, Ren-Raw; Sopranzetti, Ben J. (Journal of Financial and Quantitative Analysis, 2003)
Chen, Sean Chen, and Harry Sharma. We also benefited from discussions with our colleagues Ivan Brick, Oded Palmon, Emilio Venezian, and John Wald. We are particularly indebted to the anonymous referee and the editor, Paul Malatesta, for their valuable suggestions that greatly improve the paper. All errors are our own.